Routines in the process of organizational evolution = Rutyny w procesie organizacyjnej ewolucji - Stańczyk-Hugiet, Ewa (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article is to outline the cognitive model of organizational evolution taking into account the routines. Organizational evolution requires explanation and understanding of the mechanisms of development: variation, selection and retention. It is necessary also to define the object of evolution. The research results show that organizational routines constitute that object. As for the research purposes, it is important to determine the types of organizational routines.
Keywords: ewolucja; rutyny; różnicowanie; selekcja; evolution; routines; change; variation; selection